Motion of the MMS spacecraft relative to the magnetic reconnection structure observed on 16 October 2015 at 1307 UT - R. E. Denton; B. U. Ö. Sonnerup; H. Hasegawa; T. D. Phan; C. T. Russell; R. J. Strangeway; B. L. Giles; D. Gershman; R. B. Torbert (Geophysical Research Letters)
Abstract We analyze a magnetopause crossing by the Magnetospheric Multiscale (MMS) spacecraft at 1307 UT on 16 October 2016 that showed features of electron‐scale reconnection. For this event, we find orthonormal LMN coordinates from the magnetic field, with N and L varying respectively along the maximum gradient and maximum variance directions. We find the motion along N from the Spatio‐Temporal Difference analysis and motion along L from measured particle velocities. We locate the position of the magnetic X point, finding that MMS‐4 passed within about 1.4 km from the X point and that MMS‐3 and MMS‐2 passed within about 1.7 km and 2.4 km, respectively, from the position of maximum out of plane current.